Diabetes knowledge, attitude and practice (KAP) study among Iranian in-patients with type-2 diabetes: A cross-sectional study. Issue 1 (January 2016) - Niroomand, Mahtab; Ghasemi, Seyedeh Najmeh; Karimi-Sari, Hamidreza; Kazempour-Ardebili, Sara; Amiri, Parisa; Khosravi, Mohammad Hossein
Summary: Aim: Recent studies highlight barriers of diabetes educational programs in Iran and also present some successful experiences carried out for improving the knowledge, attitude, and practice (KAP) of type-2 diabetic patients. Hence, evaluation of patients' KAP seems to be needed. We designed a multicenter study evaluating level of KAP in type-2 diabetic patients in the capital city of Tehran and identifying variables that affect this KAP level. Methods: This multicenter analytical cross-sectional study was approved by Shahid Beheshti University of Medical Sciences Ethics Committee. Questionnaires were designed for evaluation of diabetes-related KAP in patients. After validating the questionnaires by endocrinologists, test–retest method was used for questionnaire reliability by checking in 15 diabetic patients. Two hundred type-2 diabetic patients admitted to 4 hospitals of Tehran filled out the questionnaires. Using SPSS software, the level of KAP and its confounders were evaluated in patients. Results: Two hundred type-2 diabetic patients with the mean age of 60.17 years were evaluated (106 male and 94 female). The mean diabetes duration was 13.06 years. The levels of patients' good knowledge, attitude, and practice were 61.41%, 50.44% and 52.23%, respectively. Age, treatment methods, DM duration, and existence of diabetic retinopathy had significant correlations with KAP level. Conclusions: The results of this study showed that recent educational programs in Iran improved KAP level. Patients' KAP increases as their condition worsens/progresses. Hence education should be considered as a priority for newly diagnosed patients and those with lower KAP levels before occurrence of diabetes complications.